PENGGUNAAN ALGORITMA SIMULATED ANNEALING UNTUK MENYELESAIKAN TEKA-TEKI BINARY DAN SUDOKU ( Solving Binary and Sudoku Puzzles with a Simulated Annealing Algorithm ) - Bagus Sartono (FORUM STATISTIKA DAN KOMPUTASI, 2011)
Binary and Sudoku puzzles could be seen as optimization problems by using a score  of  rules  violation  as  the  objective  function  which  is  minimized. The simulated annealing algorithm is a good alternative to solve the puzzles.  This paper  describes the  approach  which  implements  the  algorithm  and  presents the  SAS/IML  program  of  it.    Empirical  trials  show  that  the  approach  works well to find the solution of the puzzles in a satisfying run time.  Keywords : meta-heuristic, simulated annealing